2016
DOI: 10.1306/02011614222
|View full text |Cite
|
Sign up to set email alerts
|

Effective flow properties heterolithic, cross-bedded tidal sandstones: Part 2. Flow simulation

Abstract: Here we investigate the impact of mudstone drape distribution on the effective permeability 26 of heterolithic, cross-bedded tidal sandstones using three-dimensional (3D) surface-based 27 "mini-models" that capture the geometry of cross-beds at an appropriate scale. The impact 28 of seven geometric parameters has been determined: (1) mudstone fraction, (2) sandstone 29 laminae thickness, (3) mudstone drape continuity, (4) toeset dip, (5) climb angle of foreset-30 toeset surfaces, (6) proportion of foresets to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…pseudo relative permeability and pseudo capillary pressure) upscaling procedures 1,38 for dealing with small-scale volume-filling petrophysical variability. Small-scale geometrical features which occupy only a small fraction of the volume they are contained in, such as sub-seismic faults or shale-draped sedimentary structures, have received less attention and if they are considered in upscaling studies it is generally only with reference to establishing effective permeabilities due to low permeability fault rock or shale drapes 911 . However, low permeability fault rock is not the only characteristic of faults to consider, and shear displacements across sub-seismic faults can be very significant on reservoir flow.…”
Section: Introductionmentioning
confidence: 99%
“…pseudo relative permeability and pseudo capillary pressure) upscaling procedures 1,38 for dealing with small-scale volume-filling petrophysical variability. Small-scale geometrical features which occupy only a small fraction of the volume they are contained in, such as sub-seismic faults or shale-draped sedimentary structures, have received less attention and if they are considered in upscaling studies it is generally only with reference to establishing effective permeabilities due to low permeability fault rock or shale drapes 911 . However, low permeability fault rock is not the only characteristic of faults to consider, and shear displacements across sub-seismic faults can be very significant on reservoir flow.…”
Section: Introductionmentioning
confidence: 99%
“…Such intercalations have repeatedly been shown to have a significant impact on fluid flow (e.g. Jackson et al 2005;Ringrose et al 2005) and remain an area of active research (Massart et al 2016). Accordingly, the second group of papers in the Special Publication reviews and extends the literature that describes tide-influenced paralic reservoirs and their outcrop analogues.…”
Section: Tidal Heterogeneity In Paralic Systemsmentioning
confidence: 99%
“…The method to calculate effective permeability is presented in the companion paper 460 (Massart et al, 2016) and we report only the results here for the two models shown in 461…”
Section: Calculation Of Effective Permeability 459mentioning
confidence: 99%